Structural behaviour of end-plate connections on hybrid beam to cruciform column section - Tan, Boon Cheik (2020)
Cruciform column section is an innovative column section which consists of two universal beam sections where one of the beams is cut into half along its web and welded onto the web of other beam. Distinct geometrical differences compared to conventional universal H-shaped column section are that the cruciform column has smaller width to depth ratio and lower flange thickness. Its advantages as an alternative vertical compressive member were well proven by previous researchers since 2005. This study focuses on structural behaviour of flush end plate and extended end plate connections of hybrid beam to cruciform column section. Experimental tests of four flush end-plate and four extended end-plate connections on hybrid beam to cruciform column section were conducted and the results were used to validate analytical study and finite element modelling (FEM). Analytical study was conducted based on Eurocode 3: Part 1.8 component method and existing mathematical models. It was found that Eurocode 3: Part 1.8 can be used to predict initial stiffness and moment resistance of cruciform column connections. Existing mathematical models were not able to predict moment rotation behaviour of cruciform column connections but were specifically useful for predicting connection behaviour within the limit of regression model. Hence, comprehensive finite element analysis using ANSYS 14.0 on the cruciform column connections was carried out to predict the moment rotation behaviour. Initial stiffness and moment resistance of the models were in good agreement with experimental test results with percentage difference well within 20%. In terms of failure mode, the deformation shown in FEM exhibited similar pattern with experimental tests and Eurocode 3: Part 1.8. Parametric analysis was carried out using validated FEM model. Critical zones were determined through stress distribution pattern using stress ratio and verified with linear-plastic and semi-rigid partial strength connection behaviour of cruciform column connections. From the parametric analysis, it was identified that the significant parameters for cruciform column connections were beam depth, end-plate thickness, and column flange thickness. Simple mathematical functions were developed to predict moment rotation behaviour of cruciform column connections using regression analysis and were strongly supported by statistical analysis. As compared to existing finite element models, the initial stiffness and moment resistance percentage differences were well within 15% for both single bolt row flush end-plate and extended end-plate cruciform column connections. Based on these outcomes, practising engineers will be able to predict the moment rotation behaviour of cruciform column connection conveniently and accurately using the developed mathematical function.